Long-term result of transcatheter arterial embolization for liver hemangioma. Issue 49 (December 2017) - Liu, Xiaolei; Yang, Zhiying; Tan, Haidong; Huang, Jia; Xu, Li; Liu, Liguo; Si, Shuang; Sun, Yongliang
Abstract : Abstract: Transcatheter arterial embolization (TAE) is a method for the treatment of liver hemangioma, but fewer studies reported the long-term result. Retrospective study was conducted to liver hemangioma patients who received TAE. The inclusion criteria included the following: the period of follow-up was more than 5 years; and patients were followed up for less than 5 years, but received surgical treatment due to the enlargement of tumor or severe complications of TAE. The collected data included sex, age, size of the tumor, times of TAE, complications, period of follow-up, long-term result, and whether or not surgery was finally performed. Fifty-five patients were included, and the average age was 43.1 ± 8.6 years. The average size of liver hemangioma was 9.0 ± 4.3 cm. Four patients (7.3%) had severe complications after TAE, including 2 cases of biloma which were cured by surgery. The tumor size was smaller or the same in 19 patients after 5 years follow-up, and the long-term effective rate was 35.8%. The size of tumor became larger in the other 34 patients (64.2%), and 29 patients (54.7%) received surgery finally. The long-term effective rate for patients with ≥10 cm tumor and <10 cm tumor were 12.5% and 45.9%, respectively, and the difference was significant ( P  = .019). The long-term result of TAE for liver hemangioma was not satisfying, and the treatment had the risk of severe complication. For patients with asymptomatic liver hemangioma, TAE should not be conducted.